Ageing in Ghana: A Public Health and Cultural Perspective - Badasu, D.M.; Aryeetey, R.; Bitugu, B.B.; Ocansey, R. (Ageing, Physical Activity and Health: International Perspectives, 2018)
This chapter discusses the current situation of aging in Ghana from a cultural and public health perspective. There are traditionally established norms by which aging is integrated into societal living. However, due to the processes of modernization, particularly increasing urbanization and migration, these norms are being transformed rapidly in such a way that the traditional safety nets have come under severe stress. Emerging formal care systems are, therefore, expected to complement the traditional debilitated norms. However, these formal care systems are still a long way off from adequately supporting the huge unmet need for care of the elderly, especially in urban settings. Gender differences as well as local cultural norms are taken into consideration for the proposal of options and programs to adequately address the needs of the elderly and support them in their aging process, including physical activity. In the absence of structured interventions, volunteer and club activities can be promoted to keep the elderly in an active lifestyle. © 2018 selection and editorial matter, Karin Volkwein-Caplan and Jasmin Tahmaseb McConatha.